Prevention Measures and How to Handle Pre-Eclampsia (Literature Review) - Mia Cahyanti; Yanti Hermayanti; Indra Maulana (Universitas Padjadjaran, 2021)
Preeclampsia is a danger sign for pregnant women, especially at 20 weeks gestation, marked by increased blood pressure. At this time, preeclampsia is the second largest contributor to deaths globally, with preeclampsia worldwide 10% -15%. In Indonesia, there is an increase of 2% every year, indicating that adequate treatment and prevention efforts are needed. At present, most research on the prevention and management of preeclampsia discusses pharmacological treatment, not discussing nursing interventions. This Literature review aims to find out various prevention efforts for preeclampsia that are developing at this time. The research method is a literature study of research results published in 2010-2019. The strategy used to search literature is to use keywords preeclampsia, prevention, treatment methods, and nursing interventions, using Google Scholar, PubMed, Pro-Quest, Science Direct database, which reviewed using The Joanna Briggs Institute Critical Appraisal tools. The study results illustrate that there are several ways to reduce blood pressure. From 10 articles found one preventionnamely the article about consuming food and nine treatments, include: hypnotherapy, , foot massage, foot bath with warm water, cupping therapy, SEFT therapy, and murotal hearing. All articles described that intervention could reduce blood pressure, but the articles do not explain the reduction mechanism based on the intervention used. This Literature Study is expected to be information and consideration for health workers, pregnant women, and the community to handle pre-eclampsia mothers, with much interventions can doit to reduce pre-eclampsia.